Determinants of Climate Smart Agricultural (CSA) Technology Adoption in Purbalingga Regency, Central Java - Kunandar Prasetyo; Dewanti Risa Utami; Arum Tri Utami (Tarjih : Agribusiness Development Journal, 2026)
Climate change poses a growing threat to the sustainability of agricultural systems and food security across numerous countries. Climate Smart Agriculture (CSA) has emerged as a strategic instrument for simultaneously increasing agricultural productivity, strengthening adaptive capacity, and reducing greenhouse gas emissions from the agricultural sector. In Indonesia, CSA implementation has been operationalized through the Strategic Irrigation Modernization and Urgent Rehabilitation Project (SIMURP) since 2021. Despite this, the level of CSA technology adoption among farmers remains uneven and suboptimal. This study aims to analyze the determinants of simultaneous adoption of six CSA practices namely improved seed varieties, Alternate Wetting and Drying (AWD) irrigation, balanced fertilization, organic matter application, organic fertilizer use, and integrated pest management (IPM). This study was carried out in Bukateja and Kemangkon Districts, Purbalingga Regency, Central Java, Indonesia. A total of 88 respondent farmers were selected as the study sample through simple random sampling. Data were analyzed using the Multivariate Probit (MVP) model, which accommodates correlations across simultaneous adoption decisions of multiple CSA practices within a single estimation framework. The results indicate that CSA adoption decisions are significantly influenced by education, farming experience, land area, land tenure status, farmer group membership, access to credit, and farm income, with varying degrees of influence observed across individual CSA practices. Farm income uniquely predicted adoption of all six CSA technologies simultaneously, establishing financial capacity as the most critical and universal driver of CSA adoption.